2008
DOI: 10.17705/1cais.02310
|View full text |Cite
|
Sign up to set email alerts
|

Information Systems and Healthcare XXVIII: The Information Needs of Family Carers in Collaborative Healthcare

Abstract: While the important role of family carers has been increasingly recognized in healthcare service provision, particularly for patients with acute or chronic illnesses, the family carer's information needs have not been well understood or adequately supported by health information systems. In this study, we explore the information needs of a family carer by analyzing the extensive online diary of a Vietnamese family carer supporting his wife, who was a lung cancer patient. The study provides a deep understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 26 publications
4
14
0
Order By: Relevance
“…The distributed sources of emotional and informational support are significant. Those who receive the same information from multiple sources are more likely to trust that information (Griffiths et al, 2012; Long et al, 2017; McKinlay, 1973; Nguyen & Shanks, 2007), and repeated advice is more likely to be valuable when the network is relatively heterogenous and the information is from non‐similar sources (Lee & Miller, 1969).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The distributed sources of emotional and informational support are significant. Those who receive the same information from multiple sources are more likely to trust that information (Griffiths et al, 2012; Long et al, 2017; McKinlay, 1973; Nguyen & Shanks, 2007), and repeated advice is more likely to be valuable when the network is relatively heterogenous and the information is from non‐similar sources (Lee & Miller, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a pregnant woman is more likely to ask her mother for advice, rather than a spouse who has no experience with pregnancies or children (McKinlay, 1973). In turn, an individual's contribution of social capital depends on their motivations and interests (Arazy et al, 2017), and a network must have a mix of strong and weak ties to other networks to ensure lasting change (Woolcock & Narayan, 2000), which in healthcare translates to a mix of professional, institutional and carer perspectives (Nguyen & Shanks, 2007; Øydgard, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the health-care sector, Nguyen et al (2008) analysed an extensive online diary of a Vietnamese family carer supporting his wife and suggested a four-stage information journey model consisting of identification, searching, interpretation and information sharing and collaboration.…”
Section: Research On Information Journeymentioning
confidence: 99%
“…Payton and Kiwanuka-Tondo (2009) looked at HIV/AIDS pandemic among black women in terms of the spirit communicated to this population by a principal government health care web site. Nguyen et al (2008) suggested a fourstage information journey model for a family care giver including: identification, searching, interpretation and information sharing, and collaboration. Among the themes that emerged from the study were: the key role of the care giver, information filtering by the carer, information sharing and collaboration, and the influence of national culture.…”
Section: Literature Review Health Information Literature In Is Researchmentioning
confidence: 99%